The Recent Outburst of SMC X-2 as seen by Swift, MAXI and NuSTAR - Kennea, Jamie; Coe, Malcolm J.; Laycock, Silas; Bird, Tony; Bartlett, Elizabeth; Townsend, Lee; McBride, Vanessa; Corbet, Robin; Haberl, Frank; Vasilopoulos, Georgios (2016)
We present results from the latest outburst of the Be/X-ray binary system SMC X-2, which in late 2015 entered it's first X-ray outburst since 2000. SMC X-2 was first discovered in 1977 by the SAS-3 satellite, and hosts a 2.37s period pulsar. Regular, almost daily, Swift observations of SMC X-2 were performed during the entirety of the latest outburst, from first detection by MAXI to it’s rapid turn off and return back to quiescence. These observations have allowed us to measure with the flux, spectral and temporal properties of SMC X-2. Timing analysis of observation by the Swift X-ray telescope allowed us to track the evolution of the pulsar spin period, and in addition modeling of the orbital parameters of the system by measuring changes in the pulsar spin period due to Doppler effects. In addition we report on an observation of SMC X-2 taken with NuSTAR, which allowed both to better measure the continuum fit above 10 keV, and to perform a sensitive measure of the pulse profile and period of the source.